Predictive factors of tinnitus after vestibular schwannoma surgery: a case-control study - Na You; Jiashu Zhang; Ding Zhang; Yue Zhao; Jun Zhang; Bainan Xu (Chinese Neurosurgical Journal, 2024)
Abstract Background Tinnitus is very common in patients with vestibular schwannoma (VS). We analyzed the related factors of tinnitus after surgery. Methods One hundred seventy-three patients diagnosed with unilateral VS operated via the retrosigmoid approach were included in the study. All patients underwent relevant examinations and completed the THI scale before surgery and 6 months after surgery. The prognosis of tinnitus was evaluated according to the changes in THI. Results Of the 129 preoperative tinnitus patients, postoperative tinnitus resolved in 12.4%, improved in 29.5%, remained unchanged in 28.6%, and worsened in 29.5%. 18.2% of 44 patients without preoperative tinnitus appeared new-onset tinnitus postoperatively. Thirty-six patients never had tinnitus. Patients with smaller tumor sizes (≤ 3 cm) were more likely to experience preoperative tinnitus. Younger patients and those with serviceable hearing preoperatively were more likely to report their tinnitus unchanged or worsened. A new onset of postoperative tinnitus in the preoperative non-tinnitus group was found in better preoperative hearing function. Conclusions In this study, 70% of patients had persistent tinnitus after vestibular schwannoma resection. The prognosis of tinnitus was influenced by age and preoperative hearing function. Tinnitus is a bothersome symptom and is often underestimated by doctors. Assessment of tinnitus is mandatory during the management of vestibular schwannoma.